Koncepcja wartości w filozofii - szkic = The concept of the value in philosophy - sketch - Dobies, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The term value is of interest to philosophers of all ages. It gained popularity after 1870. It was perceived as something worth striving for. The values were divided, among others for good, useful, fun or perfect. The concept of value has been the subject of many areas of life. The values were divided into: moral, final, functional and aesthetic. They have become the subject of research of almost every philosophical trend, from the philosophy of axiological subjectivism through relativism, objectivism, phenomenology to personalism.
Keywords: wartości; filozofia; dobro; prawda; piękno; values; philosophy; good; truth; beauty